Multiple regression analysis to estimate height fromdynamic footprint anthropometry in Malaysia Indian sub-ethnic group - T. Nataraja Moorthy,; Rasvini Asogan,; Suresh Kumar, (Malaysian Society of Applied Biology, 2016)
Human beings are social animals. The uniqueness human body size would become the basis of what Bertillon would term anthropometry, a system of personal identification based on the theory that no two people were identical in their body measurements. Person identification is a key element in forensic investigation. Footprint is a valuable item of physical evidence encountered in crime scenes that can be used to determine the stature of an individual for the purpose of identification. There is a strong correlation exists between footprint and stature. Researchers have proved that contemporary population specific standards should be used to formulate the accurate biological profile. The present study aimed to derive multiple regression equations to estimate height from dynamic footprints among one of the Malaysian Indian subethnic group, Malayalees living in Malaysia. The study subject consists of 50 males and 60 females from Malaysian Malayalee population living in Malaysia. The footprints and heights were recorded following the standard procedure and derived multiple regression equation to estimate height from footprints for forensic application.